重组人血管内皮抑素联合化疗与单纯化疗在晚期非小细胞肺癌中疗效比较的系统评价 (Zhongguo Fei Ai Za Zhi, 2011)
BACKGROUND AND OBJECTIVE: In recent years, there has been a large number of studies and reports about the efficacy and safety of recombinant human endostatin (rh-endostatin), an anti-angiogenic drug, in treatment of advanced lung cancer. Authentic assessment of rh-endostatin treatment in lung cancer is important. The aim of this study is to assess the clinical efficacy and safety of rh-endostatin combined with chemotherapy in the treatment of patients with non-small cell lung cancer (NSCLC). METHODS: Cochrane systematic review methods were used in the data selection, and data were selected from the Cochrane Library, EMBASE, Medline, SCI, CBM, CNKI, and etc electronic database to get all clinical controlled trials. The retrieval time was March 2010. The objects of these randomized controlled trials were advanced NSCLC patients and in the experimental group was rh-endostatin combination chemotherapy, in the control group was chemotherapy alone to compare the efficacy of two groups. The quality of included trials were evaluated by two reviewers independently. The software RevMan 5.0 was used for meta-analyses. RESULTS: Fifteen trials with 1, 326 patients were included according to the including criterion. All trials were randomized controlled trials, and two trials were adequate in reporting randomization. Thirteen trials didn't mention the blinding methods. Meta analysis indicated that the NPE arm (Vinorelbine+cisplatin+rh-endostatin) had a different response rate compared with NP (Vinorelbine+cisplatin) arm (OR=2.16, 95%CI: 1.57-2.99). The incidences of severe leukopenia (OR=0.94, 95%CI: 0.66-1.32) and severe thrombocytopenia (OR=1.00, 95%CI: 0.64-1.57) and nausea and vomiting (OR=0.85, 95%CI: 0.61-1.20) were similar in the NPE arm compared with those in the NP arm. The NPE plus radiotherapy (RT) arm had a similar response rate compared with NP plus RT arm (OR=2.39, 95%CI: 0.99-5.79). The incidences of leukopenia (OR=0.83, 95%CI: 0.35-1.94) and thrombocytopenia (OR=0.78, 95%CI: 0.19-3.16) and radiation esophagitis (OR=1.00, 95%CI: 0.40-2.49) were similar in the NPE plus RT arm compared with those in the NP plus RT arm. CONCLUSION: In the treatment of advanced NSCLC, rh-endostatin in combination with platinum-based chemotherapy improve the response rate without obviously raised side effects, however, when radiotherapy are added to NPE arm or NP arm, the response rates have a similar outcome. Owing to the small sample size and poor quality of included trials, more well-designed double-blinded randomized controlled trials should be performed.